Augmented angiogenic transcription factor, SOX18, is associated with asthma exacerbation. (2nd September 2021) - Hong, Jisu; Lee, Pureun-Haneul; Lee, Yun-Gi; Leikauf, George D.; Jang, An-Soo
Abstract: Background: Asthma characterized by airway hyperresponsiveness, inflammation, fibrosis, and angiogenesis. SRY-related HMG-box 18 (SOX18) is an important transcription factor involved in angiogenesis, tissue injury, wound-healing, and in embryonic cardiovascular and lymphatic vessels development. The role of angiogenic transcription factors, SOX18 and the related, prospero homeobox 1 (PROX1) and chicken ovalbumin upstream promoter transcription factor II (COUP-TFII), in asthma has had limited study. Objective: In this study, we aimed to elucidate the role of SOX18 in the pathogenesis of bronchial asthma. Methods: Plasma SOX18 protein was measured in control subjects, and subject with stable or exacerbated asthma. SOX18, PROX1, and COUP-TFII protein was measured by western blot, and immunohistochemistry in a murine model of ovalbumin-induced allergic asthma (OVA). SOX18, PROX1, and COUP-TFII protein was measured in lung human microvascular endothelial cells (HMVEC-L) and normal human bronchial epithelial (NHBE) cells treated with house dust mite ( Der p 1). Results: Plasma SOX18 tended to be higher in subject with asthma compared to control subjects and increased more during exacerbation as compared to stable disease. In mice, OVA challenge lead to increased lung SOX18, PROX1, COUP-TFII, mucous gland hyperplasia and submucosal collagen. In NHBE cells, SOX18, PROX1 and COUP-TFII increased following Der p 1 treatment. SOX18 protein increased in HMVEC-L following Der p 1 treatment. Conclusion: These results suggest that SOX18 may be involved in asthma pathogenesis and be associated with asthma exacerbation.